ORGANIZATION OF VOCATIONAL TRAINING IN THE DON AND NORTH CAUCASUS AREAS DURING THE GREAT PATRIOTIC WAR - E. V. Panarina (Гуманитарные и юридические исследования)
The article describes the process of training in vocational institutions on the territory of the Don and North Caucasus during the Great Patriotic war. It reveals the major challenges in training and the measures to manage them. The article discusses the results of activity of factory training schools, craft and railway schools in training skilled workers.